Magnetic properties of conventional superconductors with columnar defects - Gredeskul, Sergey A.; Avishai, Yshai; Braverman, Gregory M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
Equilibrium vortex configuration in conventional type II superconductors containing short-range columnar defects is investigated theoretically. In the bulk superconductor near the upper critical field Hc2 a single defect causes a strong local deformation of the vortex lattice which has C3 or C6 point symmetry. The vortices can collapse onto attractive defect, while in the case of repulsion the regions free of vortices appear near a defect. Increasing the applied magnetic field results in an abrupt change of the configuration of vortices related to the formation of multiquantum vortices and giving rise to reentering transitions between configurations with C3 or C6 symmetry. In the case of a small concentration of defects these transitions manifest themselves as jumps of magnetization and discontinuities of the magnetic susceptibility. Columnar defects also essentially influence the magnetic properties of a mesoscopic superconducting disc. They help the penetration of vortices into the sample, thereby decreasing the sample magnetization and reducing its upper critical field. Even the presence of weak defects splits a giant vortex state (usually appearing in a clean disc in the vicinity of the transition to a normal state) into a number of vortices with smaller topological charges. In a disc with a sufficient number of strong enough defects vortices are always placed onto defects. The presence of defects lead to the appearance of additional magnetization jumps related to the redistribution of vortices which are already present on the defects and not to the penetration of new vortices.